The Influence of Safety Performance For Hauling Operators At PT. XYZ - Mayang, Mayang Rizky Rian Winney; Siwi, Siwi Dyah Ratnasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Occupational safety is a crucial issue in the mining industry, given the high risk of accidents that can occur in the field. The mining industry plays an important role in the economy of many countries, especially those rich in natural resources. The purpose of the research is to analyze the effect of safety culture and work environment on safety performance. This research uses quantitative analysis with survey methods. The sample in the study was 154 hauling operators and the analysis tool used SEM-PLS. the research results state that there is a positive and significant influence on safety culture and the work environment on safety performance. This suggests that the results of the study can provide a strong basis for companies to develop and strengthen safety culture programs that focus on increasing awareness and compliance with safety procedures among hauling operators. In addition, improvements in the design and condition of the work environment can create a safer and more comfortable working environment, which in turn will improve safety performance and operator productivity. The implications of the research show that a good safety culture and work environment significantly improve the safety performance of hauling operators at PT XYZ. To improve safety, the company should intensify safety training and rewards, improve working conditions, and adopt the latest safety technologies and procedures. With these measures, PT XYZ can reduce work incidents, increase productivity and strengthen its safety reputation.